2005
DOI: 10.1093/jn/135.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid Alleviates Nonalcoholic Fatty Liver Disease in Zucker (fa/fa) Rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the preferred term to describe the spectrum of liver damage ranging from hepatic steatosis to steatohepatitis, liver fibrosis, and cirrhosis, and it is emerging as the most common liver disease in industrialized countries. Thus, the discovery of food components that would ameliorate NAFLD is of interest. Conjugated linoleic acid (CLA), a mixture of positional and geometric isomers of linoleic acid, has attracted considerable attention because of its potentially benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 41 publications
10
58
0
1
Order By: Relevance
“…Although it is unclear why the combination of CLA with ROSI has additional effects in liver and muscle, it may be attributable to increased adiponectin levels with ROSI administration. It is possible that in the presence of adequate adiponectin, CLA increases lipid utilization and decreases lipid accumulation in tissues, similar to observations from rat studies (33)(34)(35).…”
Section: Discussionsupporting
confidence: 76%
“…Although it is unclear why the combination of CLA with ROSI has additional effects in liver and muscle, it may be attributable to increased adiponectin levels with ROSI administration. It is possible that in the presence of adequate adiponectin, CLA increases lipid utilization and decreases lipid accumulation in tissues, similar to observations from rat studies (33)(34)(35).…”
Section: Discussionsupporting
confidence: 76%
“…The adverse effects to induce fat liver and/hepatic steatosis have been also observed by other groups, and increasing studies indicate that t10, c12 isomer is the major player [9,22,97,133]. However, dietary CLA was reported to alleviate nonalcoholic fatty liver disease or hepatic steatosis in ZDF rats [134,135]. The discrepancy illustrated a relationship between the state of insulin resistance and liver-lipid metabolism, and suggested that CLA might act to favorably modify lipid metabolism in ZDF rats.…”
Section: Effects Of Pufa On the Neuroendocrine Systemmentioning
confidence: 69%
“…Previous study indicates that adiponectin has protective effects against fatty liver disease 49 . Additionally, we previously suggested that the enhanced levels of serum and liver adiponectin contribute to the alleviation of fatty liver diseases through the enhancement of lipoprotein synthesis and secretion in Zucker fa/fa rats 50 . In the present study, serum adiponectin level was signifi cantly increased by porpoise oil feeding.…”
Section: Discussionmentioning
confidence: 99%